Molecular composition of soil organic matter (SOM) regulate qualities of tobacco leaves - Xu Zhai; Long Zhang; Ruofan Wu; Mei Wang; Yanxiang Liu; Jiapan Lian; Mehr Ahmed Mujtaba Munir; Dan Chen; Lei Liu; Xiaoe Yang (Scientific Reports, 2022)
Abstract Soil organic matter (SOM) is of vital importance to soil health, and also plays a crucial role in the quality of the crops such as tobacco. However, the link between tobacco quality and SOM chemical compositions is still not well understood. To fill the information gap, we analyzed the quality of tobacco leaves and the corresponding SOM molecular compositions by electrospray ionization (ESI) coupled with Fourier transform ion cyclotron resonance mass spectrometry (FTICR-MS), that were collected from six different sites in Bijie, Guizhou Province, China. The tobacco quality variedin six sites based on their chemical compositions. SOM compounds had a remarked impact on the quality of tobacco leaves and a distinct difference in SOM composition between low-quality and high-quality tobacco leaves was observed as well. Specifically, 105 common molecular formulas were detected in three SOM compounds of high-quality tobacco, which were more than those in low-quality samples. Although amino sugar, proteins, lipids, tannins, and carbohydrates had a collective influence on the chemical composition of tobacco leaves, the effect contributed by amino sugar and tannins was more prominent. In summary, fully understanding the association between tobacco chemical composition and SOM compounds can provide new insight into the regulation of tobacco quality and the sustainable development of agriculture.